2013
DOI: 10.1016/j.ijgo.2013.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Urine-based human papillomavirus DNA testing as a screening tool for cervical cancer in high-risk women

Abstract: Objective To test the hypothesis that self-collected urine could be used to detect high-risk human papillomavirus (HPV) DNA with sensitivity and specificity comparable to those of standard cervical testing. Methods Women attending a gynecology clinic for evaluation of abnormal cytology were recruited. Fifty-two participants (21–60 years of age) collected urine samples, and clinicians collected cervical brush samples. When appropriate, cervical biopsies were obtained during colposcopy. HPV detection and typin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…Urine is an adequate alternative specimen to monitor HPV prevalence among women when there are cultural and religious hardships in obtaining genital samples (Vorsters et al, 2012) (Enerly et al, 2013) (Mendez et al, 2014). Eventhough urine samples are less sensitive compared to cervical samples, it is inexpensive and more socially acceptable for large epidemiological surveys in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Urine is an adequate alternative specimen to monitor HPV prevalence among women when there are cultural and religious hardships in obtaining genital samples (Vorsters et al, 2012) (Enerly et al, 2013) (Mendez et al, 2014). Eventhough urine samples are less sensitive compared to cervical samples, it is inexpensive and more socially acceptable for large epidemiological surveys in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the hrHPV genome in urine ccfDNA, we developed custom dualsequence capture baits to enrich samples for hrHPV DNA from 12 high-risk types (HPV16, 18,31,33,35,39,45,51,52,56,58, and 59). We used liquid-based sequence capture baits to measure the hrHPV genome in urine ccfDNA from women with and without cervical premalignant lesions.…”
Section: Patient Samplesmentioning
confidence: 99%
“…We compared samples from women with no intraepithelial lesions or malignancy (NILM) and CIN1 lesions with samples from women with CIN2 þ lesions and found that ZNF516 has 91.7% sensitivity, We then tested this panel of 3 classifiers in liquid-based cytology samples (n ¼ 67) from women in Puerto Rico, a subset of which had been previously tested for concordance of hrHPV genotype between cervical cytology and urine DNA (31). We compared samples from women with NILM and CIN1 lesions with samples from women with CIN2 þ lesions and found that ZNF516 has 72.7% sensitivity, 48.1% specificity, and an AUC of 0.63; FKBP6 has 63.6% sensitivity, 34.6% specificity, and an AUC of 0.50; INTS1 has 91% sensitivity, 35% specificity, and an AUC of 0.66.…”
Section: Identification Of Methylation Biomarkers Of Cin2mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Studies are beginning to explore the possibility of using urine testing as a non-invasive screening method to detect dangerous strains of HPV in women. [6,7] Using the current scientific knowledge, not screening women who are under the age of 21 years is now justified and recommended. [3,5] To prevent one true case of invasive cervical cancer in 20-24 year old women, the clinician would have to perform between 12,500 to 40,000 additional screening tests; a strong indication that cervical cancer is rare in this age group.…”
Section: Introductionmentioning
confidence: 99%